The Value of Leadership: Evidence from a Large-Scale Field Experiment - Florian Englmaier; Stefan Grimm; Dominik Grothe; David Schindler; Simeon Schudy (Center for Economic Studies and ifo Institute (CESifo), 2021)
Companies increasingly shift from hierarchical to team-based organizational structures. Scholars and practitioners alike have emphasized the potential of leadership to foster performance in these settings. However, the causal impact of leadership is difficult to identify, as in agile and crossfunctional teams leadership is often determined endogenously. This study exploits a unique opportunity to uncover the value of leadership in a non-routine task performed by teams with flat hierarchies. In a large-scale natural field experiment (>1200 participants in 280 teams), we randomly encourage teams to select a leader before performing a complex task. The leadership encouragement increases the fraction of teams solving the task within the given time limit by about 25% and teams' remaining times by roughly 75%. Choosing a leader not only improves performance time-wise, but also team organization, without reducing the originality of solutions. Hence, leadership encouragements can serve as a cost-effective tool to foster team performance.
Keywords: C92; C93; J33; D03; M52; 330; teamwork; leadership; non-routine analytical task; complex problem-solving; flat hierarchies